INNOVATIVE EDUCATIONAL APPROACHES: A MEANS TO ENHANCE THE ACTIVENESS OF PRIMARY SCHOOL PUPILS (Barqaror Taraqqiyot va Rivojlanish Tamoyillari, 2025)
This study explores the impact of innovative educational approaches on increasing the activeness of primary school pupils. By employing interactive, learner-centered, and technology-integrated methods, the research identifies how such approaches enhance student engagement and motivation. Findings suggest that innovative strategies not only improve participation but also foster cognitive, social, and emotional development in young learners.